The twelve cats of Christmas - Flores, Feather (Chronicle Books, 2022)
From chasing ribbons and shredding paper to cuddling by the fire and climbing the Christmas tree (uh-oh), the cute cats of this take on the classic "Twelve Days of Christmas" carol teach readers of all ages to celebrate the holiday season in festive, feline fashion. Endearing and adorable, these mischievous kitties are sure to steal your heart --and your cookies for Santa!